2010
DOI: 10.1373/clinchem.2009.136994
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein B with Incident Type 2 Diabetes in an Aboriginal Canadian Population1

Abstract: Background: Expanding evidence indicates that apolipoprotein B (apo B) is superior to LDL cholesterol as a marker of vascular disease. Although traditional lipid measures are known to predict type 2 diabetes, limited data are available regarding apo B. We assessed the association of apo B with incident type 2 diabetes and compared it with traditional lipid variables as a risk predictor in aboriginal Canadians. Methods: Of an initial cohort of 606 individuals without diabetes in 1993–1995, 540 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 15 publications
9
42
0
Order By: Relevance
“…The plasma concentration of APOB protein reflects the total number of potentially atherogenic particles 2,4 and, therefore, is predictive of high risk of coronary heart disease that may not be otherwise detected from routine lipid profile 2,[7][8][9][10] . High APOB protein level in blood is correlated with cerebrovascular and coronary artery diseases as well as increased risk of diabetes 1,3,11,12 . Variable number of tandem repeats (VNTRs), also known as minisatellites, comprise a significant portion (~3%) of the human genome 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The plasma concentration of APOB protein reflects the total number of potentially atherogenic particles 2,4 and, therefore, is predictive of high risk of coronary heart disease that may not be otherwise detected from routine lipid profile 2,[7][8][9][10] . High APOB protein level in blood is correlated with cerebrovascular and coronary artery diseases as well as increased risk of diabetes 1,3,11,12 . Variable number of tandem repeats (VNTRs), also known as minisatellites, comprise a significant portion (~3%) of the human genome 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they reported that obesity and insulin resistance explained most of the association between leptin and subsequent diabetes risk. Other studies also suggest that abdominal adiposity may modulate the association between leptin and type 2 diabetes [9,12,14,15,25].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of leptin have been shown to be independently associated with diabetes in some [8][9][10][11] but not all studies [7,[12][13][14][15]18]. Of these studies, only two were UK population based studies [7,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] The association of ApoB with incident of T2DM has been demonstrated with improved risk prediction as compared to HDL cholesterol or LDL cholesterol. [27] Moreover, insulin resistance is strongly associated with Apo B/Apo A1 ratio. [28] While conventional lipid estimations have been stated to be related to the incident of T2DM, some dispute still prevails on the nature and the degree of association.…”
Section: Discussionmentioning
confidence: 99%